A China-led comprehensive dispute settlement mechanism for the Belt and Road Initiative: is it too early?. Issue 1 (2nd January 2021) - He, Zhipeng; Zhao, Jianzhou
ABSTRACT: Since the Belt and Road Initiative (BRI) was proposed in 2013, researchers have discussed the establishment of pertinent comprehensive dispute settlement bodies or mechanisms led by China. Practices concerning the China International Commercial Court (CICC) have seemingly provided evidence that the time is ripe for China to introduce a more integrated and institutional dispute settlement system. However, such analysis partially overlooks several elements key to the efficient functioning of the BRI. This article intends to explore the feasibility of establishing a comprehensive China-led BRI dispute settlement mechanism, as a matter of policy choice based on the following aspects: whether the cooperation model and development prospects of the BRI currently support a China-led dispute settlement mechanism, whether the BRI's existing dispute settlement mechanism is irreplaceable in terms of its potential for improvement and recognition by countries, and whether China and the BRI countries have established sufficient relationships of mutual trust in terms of economic and political relations, and have a reliable legal basis for designing and participating in the new system. Based on these three perspectives, this study concludes that it is not advisable for China to hasten to establish a unified BRI dispute settlement mechanism. Instead, China should uphold the principle of openness and inclusiveness, adhere to the principle of achieving shared growth through discussion and collaboration, and efficiently manage the BRI dispute settlement issue using existing bilateral and multilateral ties with BRI countries.